Biochemical analysis of fetal fluids and cytology of the amniotic fluid of female Mocó (Kerodon rupestris) - Zogno, Maria Amélia; Miglino, Maria Angélica; Oliveira, Moacir Franco (Brazilian Journal of Veterinary Research and Animal Science, 2004)
The aim of the present work was to study certain biochemical characteristics of fetal fluids of the female mocó (Kerodon rupestris), by assesment of the following parameters present in the amniotic and allantoic fetal fluids: osmolarity, pH, calcium, phosphorous, total protein, urea, creatinina and glycose. Ten genital systems of mocós were sampled (gestation = 30-45 and 65-70 days). The amniotic and allantoic sacs were punctured and the fetal fluid obtained for posterior analysis. It was observed the following concentrations (mg/ml) in the amniotic fluid: glycose= 45,87 ± 22,38; calcium = 6,31 ± 1,24; phosphorus = 1,64 ± 0,72; creatinine = 0,45 ± 0,12; urea = 34,03 ± 5,96; total protein = 31,24 ± 16,67. In the allantoic fluid the concentrations were: : glycose = 59,17 ± 10,85; calcium = 5,58 ± 0,59; phosphorous = 1,27 ± 0,73; creatine = 0,38 ± 0,38; urea = 31,49 ± 2,28; total protein = 30,70 ± 18,39. Results obtained from the analisys of the composition of fetal fluids showed small oscillations between the amniotic and the allantoic fluids. Their concentrations, probably, are determined by the materno-fetal metabolic activity. Amniotic fluid cytology showed four cells types.